Hydro- and morphodynamic impacts of sea level rise: The Minho estuary case study - Weber de Melo, Willian (2020)
The understanding and anticipating of climate change impacts is one of the greatest challenges for humanity. It is already known that, until the end of the 21st century, the mean sea level (MSL) will rise at a global scale, but its effects at the local scale need to be further analyzed. In this context, a numerical modelling tool and a methodological approach for the river Minho estuary (NW of the Iberian Peninsula) are presented, to predict possible consequences of local MSL rise, considering the greenhouse emission scenarios RCP 4.5 and RCP 8.5. Hydrodynamic and morphodynamic impacts were analyzed considering several driving factors, such as tides, sea level rise, storm surge, wave set-up, and different river flood peak discharges, taking into account their probabilities of occurrence. The model was calibrated using in-situ data and a data assimilation tool, the OpenDA, which automates this process, allowing to reach reliable results in a considerably short time when compared with traditional techniques. The results forecast that the predicted MSL rise will reduce the flow velocity magnitude and the sediment transport into the coastal platform but will aggravate the inundation risks along the estuarine banks. In the worst scenario (RCP 8.5) the water level near the river mouth of the estuary is expected to rise 0.20 m for 50 years return period ocean water rising, and 0.60 m for 100 years return period. It was also possible to identify that floods are the most important driver for the sediment transport along the estuary, while the tide effect in the morphodynamics is restricted to the downstream estuarine region. This work demonstrated the importance of the numerical modelling tools to better understand the effects of climate change at local scales through the representation of the estuarine hydrodynamic pattern evolution for future climate scenarios.